Resources, Aspirations, and Emerging Multinationals - Xie, E.; Huang, Y.; Peng, Mike; Zhuang, G. (2016)
Drawing on the resource-based view and the behavioral theory of the firm, we examine how resources and aspirations affect rapid internationalization of firms from emerging economies. Using a 5-year panel from 257 publicly listed manufacturing firms from China, we find that neither technological resources nor marketing resources—two knowledge-based drivers traditionally identified to be behind internationalization—directly drive these firms’ growth in internationalization. Instead, we find that emerging multinationals’ performance relative to aspirations has a U-shaped impact on their growth in internationalization. In addition, technological resources amplify the U-shaped effect of performance relative to aspirations, while marketing resources weaken the effect.